SURG-01. DEVELOPMENT OF MURINE MODEL OF LASER INTERSTITIAL THERMOTHERAPY (LITT) FOR BRAIN TUMORS. (14th November 2022) - Frain, Matthew; Ebrahim, Ghaidaa; Tomdio, Macaulay; Mendez-Gomez, Hector; Thomas, Nagheme; Karachi, Aida; Dastmalchi, Farhad; Flores, Catherine; Mitchell, Duane; Bova, Frank; Rahman, Maryam
Abstract: The objective of this study was to develop and test a murine system for delivery of laser interstitial thermotherapy (LITT). A system was built that allows for stereotactic placement of the laser into a mouse brain and real-time thermometry with a custom-made thermometer holder. Tissue heating curves for Laserglow Technologies 1064nm laser experiments testing tissue heating were performed by placing the laser in tissue and temperature monitoring via thermal probe. The laser was adapted for use with a stereotactic frame utilizing a system with a Hamilton syringe and a holder for consistent and precise placement of the thermal probe. The murine experiments were performed with C57BL/6 mice and samples were analyzed with H&E staining. First, ideal laser output was established using chicken breast. Laser dial setting of 4.38 successfully achieved slow tissue heating while a setting of 4.43 and 4.50 accomplished it rapidly, reaching a thermal ablative temperature of 43C in three and a half minutes. Next, a system for laser placement into the murine brain using the stereotactic frame was built revealing that the thermometer probe would require a separate system for consistent and precise measurements of heating. A thermometer probe holder was designed and fashioned via trigonometric calculations that allowed for thermal monitoring within 3mm spacing during laser ablation. Mice were anesthetized and treated with laser ablation at laser output of 4.38 and 4.43. H&E staining of the brain tissue demonstrated clear evidence of localized ablation identifiable by visible lesions on the H&E slides. The successful development of the stereotactic system for acquisition of tissue heating data coupled with evidence of successful live brain tissue ablation in a murine model via LITT proves that our protocol is ready for research of therapeutic combinatorial effects on live tumor bearing mice.